Climate Change and Mandatory Carbon Reporting: Impacts on Business Process and Performance. (10th December 2017) - Tang, Samuel; Demeritt, David
Abstract: As part of their annual directors' report, UK‐listed companies are now required to disclose their greenhouse gas emissions and account publicly for their contributions to climate change. This paper uses this mandatory carbon reporting to explore wider debates about corporate social responsibility and the purpose, practice, and impacts of such non‐financial reporting. Empirically, it combines documentary analysis of the carbon reporting practices of 176 large firms listed in the FTSE100 and/or subject to the UK government's adaptation reporting power with 60 interviews with stakeholders involved in carbon reporting. Firms disclose their emissions in response to financial incentives, social pressure and/or regulatory compulsion. In turn, rationales shape whether and how carbon reporting influences internal business processes and performance. The importance of reporting to the bottom line varies by sector depending on two variables – energy intensity and economic regulator status – yet there is limited evidence that carbon reporting is driving substantial reductions in emissions. Findings suggest reasons for caution about hopes for 'nudging' firms to improve their environmental performance and social responsibility through disclosure requirements.